Structural changes in arboreal ant assemblages (Hymenoptera: Formicidae) in an age sequence of cocoa plantations in the south-east of Bahia, Brazil - da Conceicao, E.; Delabie, J.; Della Lucia, T.; de Oliveira Costa-Neto, A.; Majer, Jonathan (Wiley Online Library, 2015)
A study of succession of ant species in plantations of different ages and development may assist with our understanding of the dynamics of their assemblages. The aim of this study was to characterise the relationship between development of Brazilian cocoa plantations and the nature of their dominant ant assemblages. A chronosequence of cocoa plantations aged 1, 3, 4, 8, 15 and 33 years was sampled by several methodologies. Data were analysed in terms behavioural dominance and Berger-Parker’s dominance index (here based on frequency data), and also by principal component analysis and analysis of co-occurrence. Apart from lower numbers of species being found in the 1-year-old plantation, there was no consistent trend in ant richness with plantation age. According to the criteria we adopted, only one species reached behavioural dominance in most age classes of plantation, although this increased to three in the 8-year-old one, before declining to zero in the oldest plantation. No species reached Berger-Parker’s dominance in the youngest plantation, whereas all other age classes contained one to three dominants. Particular species showed non-age-related variations in their degree of Berger-Parker’s dominance and this could in part be related to which species initially colonised the plantation. Principal component analysis axis 1 was partly related to plantation age, indicating an age-related change in assemblage composition. Ant species co-occurrence could only be effectively detected in cocoa plantations from 3 to 15 years of age. The arboreal ant assemblage is dynamic in nature, with the competitive hierarchy among species oscillating along the cocoa development chronosequence. The assemblage structure could be influenced by the initial founding ants, as well as by the invasive Monomorium floricola.